Hybrid Vigour and Inbreeding Depression for Yield and its Component Traits in Bitter Gourd (Momordica charantia L.) - Radha Rani, K.; Reddy, K. Ravinder; Surender Raju, CH. (International Journal of Bio-resource and Stress Management, 2015)
Twenty eight crosses generated using eight genotypes viz., IC-033227, IC-044417, IC-044438, IC-045339, IC-085622, IC-470550, IC-470558 and IC-470560 were evaluated to study the extent of heterosis and inbreeding depression for yield and yield attributing characters in bitter gourd at College of Horticulture, Rajendranagar, Hyderabad. The experiment was laid out in a randomized block design with three replications. The results revealed that most of the crosses showed significant heterosis over mid parent and better parent for the traits studied. The maximum heterosis (over mid and better parents) for yield vine-1 was observed in IC-044438×IC-045339 (96.03 and 58.48%) followed by IC-044417×IC-470558 (60.24 and 54.01%), IC-045339×IC-470558 (54.09 and 38.70%) and IC-045339×IC-085622 (52.64 and 32.44%). Furthermore these crosses were found superior for one or more fruit characters like average fruit weight and fruit length (IC-044438×IC045339) and number of fruits vine-1 (IC-044417×IC-470558). The crosses showing significant heterosis for yield also revealed inbreeding depression thus indicated major involvement of non-additive gene action in the inheritance of yield vine-1. However for days to 1st female flower and node number at 1st female flower, significant heterosis in desired direction was observed in IC-045339×IC- 470550 (-9.57 and -7.65%) and IC-044438×IC-045339 (-20.34 and -15.14%) respectively had no inbreeding depression. These results suggesting that it would be useful to utilize these promising cross combinations which showed superior performance for earliness, fruit yield and other yield attributes for exploitation of heterosis. Hence, methods like heterosis breeding, recurrent selection and progeny selection may be employed for improvement in bitter gourd.